Multimodal on Quiper Online Tutoring Adversisment - Nurhasanah Purba; Agung Lasmono; T. Thyrhaya Zein (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
This study aims to analyze the aspects contained in quipper online tutoring advertisements using multimodal analysis. This study uses qualitative methods to describe the object of research in accordance with what was observed and captured from the data obtained. In addition, the purpose of this method is to assist the research process by providing a more accurate picture. The multimodal concept used in this study is Cheong. The research results show that. There are 5 components in this advertisement, namely linguistic, visual, audio, spatial and genre, which in the linguistic analysis of speech used both oral and written verbal contain meanings that are easily understood by the public. In visual analysis, there are 5 visual stages that appear in this advertisement.